A Study on ICT Integration in Vocational Education: Implications for Student Learning Experiences and Alignment with the National Education Policy 2020 - Ravichandran, R; Raman, Rakesh Kumar (Indian Journal of Educational Technology, 2025)
This study investigates the integration of Information and Communication Technology (ICT) into vocational education, aiming to enhance students’ learning experiences and prepare them for the demands of the modern workforce. Utilising a mixed-methods approach, data were collected from vocational teachers and students across various states in India. The study explores the benefits, challenges, and implications of ICT integration in vocational education. Findings reveal that effective integration of ICT can provide interactive and engaging learning environments, addressing disparities in access and usage while boosting students’ confidence and competence in utilizing technology. Furthermore, understanding students’ motivation and providing teacher support are crucial for promoting student engagement and enhancing vocational education outcomes. The study emphasises the importance of tailored teacher training programs and ongoing professional development initiatives to optimise ICT utilisation. Overall, the study underscores ICT’s transformative potential in enriching vocational learning experiences and preparing students for success in the 21st-century workforce.